2019
DOI: 10.1136/bmjopen-2018-025076
|View full text |Cite
|
Sign up to set email alerts
|

Systematic scoping review protocol for clinical prediction rules (CPRs) in the management of patients with spinal cord injuries

Abstract: IntroductionThe upsurge in the use of clinical prediction models in general medical practice is a result of evidence-based practice. However, the total number of clinical prediction rules (CPRs) currently being used or undergoing impact analysis in the management of patients who have sustained spinal cord injuries (SCIs) is unknown. This scoping review protocol will describe the current CPRs being used and highlight their possible strengths and weaknesses in SCI management.Methods and analysisArksey and O’Mall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…In some epidemiological contexts, such as the one we are focusing on, it is important to assess studies' qualities even if it does not add to the methodological strength of the scoping review itself. For example, in an ongoing scoping review, authors aimed to assess the number of validated prediction rules that exist for spinal cord injury management and to provide evidence of the psychometric properties of these prediction rules, especially with regard to its clinical impact [17]. Although their scoping approach does not aim to assess the overall effectiveness of these prediction rules in their respective settings, their systematic appraisal of data quality will help readers make informed use of their findings.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In some epidemiological contexts, such as the one we are focusing on, it is important to assess studies' qualities even if it does not add to the methodological strength of the scoping review itself. For example, in an ongoing scoping review, authors aimed to assess the number of validated prediction rules that exist for spinal cord injury management and to provide evidence of the psychometric properties of these prediction rules, especially with regard to its clinical impact [17]. Although their scoping approach does not aim to assess the overall effectiveness of these prediction rules in their respective settings, their systematic appraisal of data quality will help readers make informed use of their findings.…”
Section: Methodsmentioning
confidence: 99%
“…A third reviewer (RN, GN) will review any studies where there is a discrepancy between the two independent reviewers that they are not able to resolve. Although scoping reviews do not usually include quality assessment, when dealing with epidemiological models, it is important to pay attention to the methodology and the design of original studies [17]. Two independent reviewers trained in epidemiology (RN, IF, GN) will be involved in assessing potential selection and information bias in selected studies and will discuss the potential impact of bias on the features and accuracy of selected models.…”
Section: Data Extractionmentioning
confidence: 99%
“…We only included prospective studies with quantitative data for at least one prediction prognostic model of diabetes complications and for which there was reported evidence of internal and/or external validation 18. We explored potential biases to better inform readers and knowledge users who may be concerned with the reliability and consistency of diverse data 19 20…”
Section: Eligibility Criteriamentioning
confidence: 99%
“…23,24 Because diabetes risk complications are often evaluated in epidemiological studies, we additionally explored potential biases in original studies. Previous work using a similar approach suggested that it may help readers make informed use of findings 25 and alleviate the potential challenge of evaluating reliability and consistency in data of diverse nature. 26…”
Section: Eligibility Criteriamentioning
confidence: 99%